Madrasah sebagai Sistem Sosial: Dinamika Interaksi Kelas dan Peran Stakeholder dalam Membentuk Ekosistem Pembelajaran Islami - Usnul Lestari; Muhammad Nur Maallah; Syamsuriah Syamsuriah; Taufik Taufik (FKIP UNSULTRA, 2025)
Madrasahs, as Islamic educational institutions, function not only as places for the transfer of knowledge but also as complex social systems, where interactions between members play a crucial role in shaping the quality of learning. This literature review examines the dynamics of classroom interactions and the roles of various stakeholders teachers, students, parents, and madrasah administrators in creating an effective Islamic learning ecosystem. Previous studies have shown that positive interactions between teachers and students, collaboration between stakeholders, and a supportive social environment in madrasahs contribute to the development of students' character, religiosity, and academic competence. The method used in this research is a qualitative literature review, analyzing journals, books, and scientific articles from 2018 to 2024 that are relevant to madrasahs as Islamic social and learning systems. The results reveal that adaptive, communicative, and collaborative classroom interactions strengthen the process of socializing Islamic values, while the active involvement of parents and madrasah administrators supports the creation of a conducive learning environment. The discussion emphasizes the importance of synergy between academic, social, and religious dimensions in building a holistic learning ecosystem. In conclusion, madrasas, as social systems, require effective classroom interaction management and integrated stakeholder participation to produce quality Islamic education. The implications of this study can inform the development of policies, programs, and pedagogical practices in modern madrasas.